(untitled) (ModaPalavra e-periódico, 2019)
The article aims to discuss the body’s limits of issues as proposed by the Brazilian artist Lygia Clark, through its sensory works (1965/1969). To this end, a documentary research on art critics texts was held, newspapers and letters of the artist during the period of its production to more recent exhibitions. The body became part of the work, allowing the questioning of sensations that are imposed by instruments (sense objects) and areas where they operate. The work ofthese artists began to question not only what art is, but also where these pieces could be displayed. Reader of Merleau-Ponty philosopher, Clark proposed phenomenological, participatory experiences, which did not allow the passive spectator before the subject’s movements and body. Thus, Lygia Clark stood before the limits, sensory and ethical body, the interaction between body and work through questioning or even reversal of gendered performances.